Pengaruh Corporate Social Responsibility Terhadap Stock Return Dengan Firm Performance Sebagai Variabel Mediasi Pada Perusahaan Yang Terdaftar Di Bursa Efek Indonesia - Agnes Runtulalu; Adwin Surja Atmadja (Business Accounting Review, 2017)
The purpose of this study was to know the direct affect of Corporate Social Responcibility toward stock return with firm performance as a mediating variable. This study used quantitative method by using secondary data of annual report and sustainability report. This study used companies listed in Indonesia stock exchange and published corporate social responsibility report in accordance with global reporting initiative (GRI) standard. The sample of this study was 18 companies listed in Indonesian Stock Exchange from 2010-2015.            The data analysis method was tested by using Generalized Least Square (GLS) with the STATA 13 software. The result of this study revealed that: corporate social responcibility had direct significant positif affect toward stock return. Firm performance could not become mediating corporate social responsibility toward stock return. While the control variable debt to equity had no affect to stock return, but had significant negative affect to firm performance. In the other hand, the control variable firm size had significant positive affect to stock return, but had significant negative affect to firm performance.